2013
DOI: 10.1371/journal.pone.0067699
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of DNA Extraction Methods in Analysis of Salivary Bacterial Communities

Abstract: Culture-independent high-throughput sequencing-based methods are widely used to study bacterial communities. Although these approaches are superior to traditional culture-based methods, they introduce bias at the experimental and bioinformatics levels. We assessed the diversity of the human salivary microbiome by pyrosequencing of the 16S rDNA V1–3 amplicons using metagenomic DNA extracted by two different protocols: a simple proteinase K digestion without a subsequent DNA clean-up step, and a bead-beating mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
69
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(82 citation statements)
references
References 38 publications
12
69
0
1
Order By: Relevance
“…These findings are consistent with previous studies of the salivary microbiome in healthy subjects, although Neisseria was less prominent in our findings compared with other reports (37)(38)(39)(40)(41). Streptococcus, Prevotella, Rothia, and Veillonella were also detected in high RA in ES and IS samples, consistent with previous studies of CF airway samples using molecular approaches and anaerobic cultures (7,9,10,13,42).…”
Section: Original Researchsupporting
confidence: 93%
“…These findings are consistent with previous studies of the salivary microbiome in healthy subjects, although Neisseria was less prominent in our findings compared with other reports (37)(38)(39)(40)(41). Streptococcus, Prevotella, Rothia, and Veillonella were also detected in high RA in ES and IS samples, consistent with previous studies of CF airway samples using molecular approaches and anaerobic cultures (7,9,10,13,42).…”
Section: Original Researchsupporting
confidence: 93%
“…The variations in the resultant microbial profiles in different studies due to methodological disparities make comparisons difficult and not very meaningful (Mai and Draganov, 2009). Although the results of a few studies available to date have shown no significant effects of different DNA extraction methods on the resultant bacterial profiles of biological samples (Peng et al, 2013, Wagner Mackenzie et al, 2015, a number of workers have recognised and called for a consensus and a universal DNA extraction method for microbiome analyses to overcome the challenges and misrepresentation inherent in using disparate techniques (Abusleme et al, 2014, Claassen et al, 2013, Henderson et al, 2013, Kennedy et al, 2014, Lazarevic et al, 2013, Maukonen et al, 2012, Walker et al, 2015, Yuan et al, 2012.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…To determine how much of the DNA extracted from each of our collection techniques originated from bacteria rather than the host, we performed quantitative PCR by using bacterial-or human-specific primer sets. 17,18 We found that 4-5% of the DNA extracted from our brushes and swabs was of bacterial origin, whereas only ϳ2% of the DNA from the tissue samples was bacterial ( Table 2).…”
Section: Comparison Of Collection Methodsmentioning
confidence: 92%
“…17 Bacterial 16S rRNA primers used were the following: F 5Ј-ACTCCTACGGGAGGCAGCAGT-3Ј, R 5Ј-ATTACCGCGGCTGCTGGC-3Ј; program: 10 minutes at 95°C, followed by 40 cycles of 95°C for 30 seconds and 68°C for 1 minute. 18 All reactions were performed in triplicate by using a Rotogene RG-3000 (Qiagen, Hilden, Germany). Standard curves were generated by using known concentrations of Human Male Genomic (EMD Millipore, Billerica, MA) and Escherichia coli (Affymetrix, Santa Clara, CA) DNA.…”
Section: Quantitative Polymerase Chain Reactionmentioning
confidence: 99%